Stannous chloride reduction–filtration for hexavalent and total chromium removal from groundwater. Issue 2 (5th March 2020) - Kennedy, Anthony; Croft, Rachel; Flint, Leah; Arias‐Paić, Miguel
Abstract: Hexavalent chromium (Cr(VI)) reduction using stannous chloride (SnCl2 ) has emerged as a possible alternative to chromium treatment technologies such as strong base anion exchange. In an effort to target not only Cr(VI) reduction but, ultimately, total chromium (Cr(T)) removal, SnCl2 addition followed by rapid sand filtration was tested at the pilot scale on a groundwater with a naturally occurring Cr(VI) concentration of 0.090 mg/L. A SnCl2 dose of 1.5 mg/L, followed by filtration, was able to consistently remove Cr(T) to less than 0.010 mg/L following an initial ripening period, with limited head loss for 10 sequential 17‐ to 25‐hr filter runs. Total tin and turbidity removal were similar, decreasing to below 0.050 mg/L and raw water levels, respectively. Analysis of filter sand following backwashes and three different material pipe segments that were exposed to unfiltered water dosed with SnCl2 indicated the accumulation of Cr and Sn on surfaces, which remains a concern.